Association between cognitive functioning and microbiota-gut-brain axis mediators in a memory clinic population - Singh Solorzano, Claudio; Festari, Cristina; Mirabelli, Peppino; Mombelli, Elisa; Coppola, Luigi; Luongo, Delia; Naviglio, Daniele; Soricelli, Andrea; Quattrini, Giulia; Salvatore, Marco; Pievani, Michela; Cattaneo, Annamaria; et al. (Frontiers in Cellular Neuroscience, 2025)
IntroductionA growing body of evidence recognises the role of signaling molecule of the microbiota-gut-brain axis (MGBA) in cognitive impairment (CI), but data on the link with alterations in specific cognitive domains are limited. We compared the functioning in several cognitive domains (i.e., memory, visuo-constructional, executive, and language) among cognitively unimpaired (CU) subjects, patients with CI due to Alzheimer’s disease (CI-AD) and not due to AD (CI-NAD). Then, we investigated the association of these cognitive domains with the gut microbiota (GM), MGBA mediators, and neurodegeneration-related markers.Materials and methodsThe study included 34 CI-AD, 38 CI-NAD, and 13 CU. Memory, visuo-constructional, executive, and language domains were assessed using composite measures. Faecal GM composition was inferred using 16S rRNA gene sequencing. MGBA mediators included the blood quantification of bacterial products (lipolysaccharide, LPS), cell adhesion molecules indicative of endothelial damage, vascular changes or overexpressed in response to infections, and pro- and anti-inflammatory cytokines. Neurodegeneration-related markers included plasma phosphorylated tau (p-tau181), neurofilament light chain (NfL), and glial fibrillary protein (GFAP).ResultsThe CI-NAD and CI-AD groups had significantly lower scores than the CU group for all cognitive domains (p < 0.043). Associations of MGBA modulators with cognitive functioning included pro-inflammatory cytokines, markers of endothelial dysfunction or overexpressed in response to infection in both groups of patients (|ρ| > 0.33, ps < 0.042). In the CU and CI-AD pooled group, lower cognitive functioning was specifically associated with higher abundance of Dialister and Clostridia_UCG-014, higher levels of LPS and with all neurodegeneration markers (|ρ| > 0.32, p < 0.048 for all). In the CU and CI-NAD pooled group, lower cognitive performance was associated with lower abundance of Acetonema, higher abundance of Bifidobacterium, [Eubacterium]_coprostanoligenes_group and Collinsella, and higher levels of vascular changes (|ρ| > 0.30, p < 0.049).DiscussionThese results support the hypothesis that gut dysbiosis and MGBA mediators may have distinct effects on cognitive functioning and different mechanisms of action depending on the disease.